(untitled) (Journal of Pharmaceutical Negative Results, 2022)
According to World Health Organization (WHO, 1972), Anaemia is defined as, “a condition in which the haemoglobin concentration in the blood is below a defined level, resulting in a reduced oxygen carrying capacity of red blood cells”. MATERIALS AND METHODS: The haemoglobin values were taken from the complete hemogram done in Semi Autoanalyser. The hemogram of patients with normal and less than normal haemoglobin concentration were grouped and analysed for anaemia, with the reference haemoglobin values as per the WHO guidelines. Result and Discussion: The overall anaemia prevalence was found to be 52.8% (206) with 23% (90) Male and 29.8% (116) female (Figure 2). Also the prevalence of anaemia among male population was 43.1% and among female population was 64.1%. This shows almost fifty percent of the population of the same sex are anaemic, which shows a slight increase in male population compared to the surveys conducted previously. The mean haemoglobin concentration was found to be 11.75 g/dl. Also it was found that there is a statistically significant difference between men and women anaemic status with Chi-square value of 7.46 and p = 0.01.Conclusion:Since anaemia has its adverse effects advanced before it is clinically apparent, early screening and implementation of measures like medicinal iron, food fortification with iron and nutritional education are necessary to control it.